2020
DOI: 10.1021/acs.analchem.9b05536
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding between Tetrahydrocannabinol and Vitamin E Acetate in Unvaped, Aerosolized, and Condensed Aerosol e-Liquids

Abstract: Vitamin E acetate (VEA) has recently been identified as a potential chemical of concern in the investigation of e-cigarette, or vaping, product use associated lung injury (EVALI). According to the Centers for Disease Control and Prevention (CDC), most patients report a history of using tetrahydrocannabinol (THC)-containing ecigarette or vaping products; approximately 50% of the THCcontaining vaping products examined by the Food and Drug Administration (FDA) in this investigation have been found to contain VEA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 15 publications
3
22
0
Order By: Relevance
“…The highest total VOCs were released by the vape cartridges followed by MCT oil, mineral oil, and VEA compared to air, suggesting carbonyl stress by these compounds. These VOCs in e-cig cartridges can generate toxic compounds, such as THC/VEA carbonyl complexes and ketene, during pyrolysis, leading to lung damage [17,18]. In this study, we also observed significant acellular and cellular ROS generation by cartridges and their major components.…”
Section: Resultssupporting
confidence: 57%
“…The highest total VOCs were released by the vape cartridges followed by MCT oil, mineral oil, and VEA compared to air, suggesting carbonyl stress by these compounds. These VOCs in e-cig cartridges can generate toxic compounds, such as THC/VEA carbonyl complexes and ketene, during pyrolysis, leading to lung damage [17,18]. In this study, we also observed significant acellular and cellular ROS generation by cartridges and their major components.…”
Section: Resultssupporting
confidence: 57%
“…The highest total VOCs were released by the vape cartridges followed by MCT oil, mineral oil, and VEA compared to air, suggesting carbonyl stress by these compounds. These VOCs in e-cig cartridges can generate toxic compounds, such as THC/VEA carbonyl complexes and ketene, during pyrolysis, leading to lung damage [17,18]. In this study, we also observed signi cant acellular and cellular ROS generation by cartridges and their major components.…”
Section: Discussionsupporting
confidence: 58%
“…Small particles penetrate deep into the lungs depositing in the alveolar region (Heyder et al 1986). Also, the aerosol may include toxic chemical constituents that could be formed from chemical reactions of VEA or THC at the high temperatures used in vaping (Wu and O'Shea 2020;Lanzarotta et al 2020). While reactions involving the common e-liquid solvents propylene glycol (PG) and vegetable glycerol (VG) at corresponding vaping conditions have been studied extensively and showed presence of toxic compounds in e-cigarette emissions (Khlystov and Samburova 2016;Talih et al 2019;Son et al 2020;Uchiyama et al 2020), the products formed from VEA or THC (and temperature of their vaping) are largely unknown.…”
Section: Introductionmentioning
confidence: 99%